Calorific Value of Several Types of Wood Through Proximate Analysis and Chemical Components Approach - Fauzan Fahrussiam; Dini Lestari; Rima Vera Ningsih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The most potential biomass to be developed with a high lignocellulose content is wood. Calorific value estimation based on the results of biomass analysis such as the proximate test can be used as an alternative to predict the calorific value accurately, quickly, and economically. Therefore, in this study, it is important to measure the calorific value simply using the proximate method with an analytical approach to the chemical content of the raw material. This study used three species of wood consisting of jabon (Anthocephalus cadamba Miq), ulin (Eusideroxylon zwageri), and api- api (Apicennia sp.). This study's chemical components that eximined in this study consist of extractive, holoselulose, and lignin content. The proximate analysis consists of volatile matter content, ash content, fixed carbon, and calorific value. The results show that ulin wood has the highest calorific value (20.13 MJ/kg), then api-api wood and last jabon wood. The high amount of calorific value is contributed by the high value of lignin, extractive, and fixed carbon.